Influence of phosphorus and zinc nutrition on yield and nutrient uptake in wheat (Triticum aestivum) and their residual effect on greengram (Vigna radiata) - Singh, Sandeep; Chauhan, Tahir Mohd; Singh, Vinay (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during 2014-16 at farmers' field in Panwari village of Agra district (UP) to study the direct and residual effects of phosphorus and zinc levels on yield, quality and nutrient uptake in wheat (Triticum aestivum L.) - greengram (Vigna radiata L.) cropping system using treatment combination of phosphorus (0, 30, 60 and 90 kg P2O5/ha) and zinc (0, 2, 4 and 6 kg/ha). The results revealed that the application of 60 kg P2O5/ha to wheat crop recorded significantly highest plant height (102.7 cm) and test weight (43.9 g). Phosphorus application in preceding wheat crop at 90 kg P2O5/ ha was found to be best for growth and yield attributes of greengram. Wheat crop responded significantly up to 60 kg P2O5/ ha by producing 5.39 t grain and 7.59 t straw/ ha. The residual effect of P in greengram was significant at 90 kg P2O5/ ha and grain and straw yield increments were to the extent of 15.8 and 12.0 %, respectively. Wheat crop responded to zinc application and 4 kg Zn/ ha could be adjudged response level. The residual effect of 6 kg Zn/ ha on succeeding greengram crop produced 12.3 and 7.1% higher grain and straw yield over control. Protein content in wheat and succeeding green gram increased significantly with P and Zn application but P was more effective in improving protein content in both the crops. There was a significant increase in protein yield of wheat and greengram with both the elements. Application of P and zinc showed substantial increase in P and Zn uptake by wheat and succeeding greengram crop over control. Nitrogen uptake by both the crops also improved significantly with these elements. The residual available P and Zn status in post harvest soil improved with the application of respective elements. Thus, application of 60 kg P2O5/ha along with 6 kg Zn/ha in wheat were optimum doses for obtaining higher productivity, produce quality and residual P and Zn in soil under wheat-green gram cropping sequence.